Photoshop for right-brainers : - Ward, Al (Wiley, 2006)
Are you an artist or photographer who views Photoshop as a tool for creative expression rather than a piece of software? Then you'll embrace Photoshop master Al Ward's original approach to the art of photo manipulation. Photoshop for Right-Brainers 2nd Edition is an update to Al Ward's unique guide, with new projects, new images, and a new lower price. It goes beyond cookie-cutter techniques and teaches you how to harness Photoshop's powerful features to make your own original work. The CD contains 400-plus Photoshop Actions, a value-add that helps you cut tedious tasks out of your workflow, freeing up time for more right-brain work.